More than Just an Immunosuppressant: The Emerging Role of FTY720 as a Novel Inducer of ROS and Apoptosis. (28th March 2018) - Takasaki, Teruaki; Hagihara, Kanako; Satoh, Ryosuke; Sugiura, Reiko
Abstract : Fingolimod hydrochloride (FTY720) is a first-in-class of sphingosine-1-phosphate (S1P) receptor modulator approved to treat multiple sclerosis by its phosphorylated form (FTY720-P). Recently, a novel role of FTY720 as a potential anticancer drug has emerged. One of the anticancer mechanisms of FTY720 involves the induction of reactive oxygen species (ROS) and subsequent apoptosis, which is largely independent of its property as an S1P modulator. ROS have been considered as a double-edged sword in tumor initiation/progression. Intriguingly, prooxidant therapies have attracted much attention due to its efficacy in cancer treatment. These strategies include diverse chemotherapeutic agents and molecular targeted drugs such as sulfasalazine which inhibits the CD44v-xCT (cystine transporter) axis. In this review, we introduce our recent discoveries using a chemical genomics approach to uncover a signaling network relevant to FTY720-mediated ROS signaling and apoptosis, thereby proposing new potential targets for combination therapy as a means to enhance the antitumor efficacy of FTY720 as a ROS generator. We extend our knowledge by summarizing various measures targeting the vulnerability of cancer cells' defense mechanisms against oxidative stress. Future directions that may lead to the best use of FTY720 and ROS-targeted strategies as a promising cancer treatment are also discussed.